PENGARUH KEPEMILIKAN MANAJERIAL, KEPEMILIKAN INSTITUSIONAL, DAN KEBIJAKAN HUTANG TERHADAP TAX AGGRESSIVE (Studi Empiris Pada Perusahaan Transportasi yang terdaftar di Bursa Efek Indonesia Periode 2011-2013) - Jeane Atari; Azwir Nasir; Elfi Ilham (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
This study aimed to determine the influence of managerial ownership, institutional ownership and debt policy on the tax aggressive. Independent variables used in this study are managerial ownership, institutional ownership and debt policy, while the dependent variable in this study is tax aggressive are measured using Effective Tax Rate (ETR). Populations used in this study is transportation companies listed on IDX 2011-2013 where the total population is used by 14 companies. The sampling technique used was purposive sampling technique in which the number of observations obtained this study was 42 (14x3). Data analysis conducted with multiple regression model with help of software SPSS version 20,0. Of the result of the testing that has been done, the partial regression test (t test) showed that the independent variables managerial ownership, institutional ownership and debt policy which has a significant influence on tax aggressive.Keywords : Managerial Ownership, Institutional Ownership, Debt Policy, Tax Aggressive, and Effective Tax Rate